Cardiac Etiologies of Hydrops Fetalis - Yuan, Shi-Min (Zeitschrift für Geburtshilfe und Neonatologie, 2017)
Cardiac etiologies of hydrops fetalis have been a topic of concern due to challenging perinatal management. The common cardiac etiologies leading to hydrops fetalis include structural cardiac anomalies, cardiac dysrhythmias, cardiac tumors, cardiomyopathy and myocarditis. The mechanisms of cardiogenic hydrops fetalis may be: 1) elevation of atrial pressure and volume overload, 2) decrease of cardiac output, and 3) development of congestive heart failure. The diagnosis of hydrops fetalis was usually made at 19–36 gestational weeks, when ultrasound is a highly effective diagnostic method. Intrauterine interventions for certain congenital heart defects, maternal transplacental or direct fetal medications and fetal pacing placement for cardiac arrhythmias, and fetal or postnatal tumor resections are important progressions of etiologic treatment for hydrops fetalis. Treatment strategies for hydrops fetalis per se are usually ultrasound-guided pericardiocentesis and feto-amniotic shunting, whereas reaccumulation may require further interventions in utero or postnatally. Hydrops fetalis often carries a poor prognosis, and mortality remains high. Current developments in the management of hydrops fetalis should encourage physicians to attempt further fetal interventions.
Keywords: cardiac arrhythmias; congenital heart defects; hydrops fetalis